IMPLEMENTASI MBKM “MENGAJAR DI SATUAN PENDIDIKAN” DI TAMAN KANAK-KANAK NEO GENESIS - Dwiyanti, Ni Made Christine; Karta, Ni Luh Putu Agustini; Suarthana, I Ketut Putra; Asih, Anak Agung Ketut Sri (Universitas Triatma Mulya, 2024)
This community service learning program is an implementation of the Independent Learning Independent Campus Learning (MBKM)